Synthesis, Spectral Characterization and Evaluation of Pharmacodynamic Activity of Copper and Nickel Complexes of Ethambutol Dihydrochloride - M. Mathrusri Annapurna; M. E. Bhanoji Rao; B. V. V. Ravi Kumar (E-Journal of Chemistry)
Nickel and copper complexes of ethambutol [EB] were synthesized and characterized. On the basis of spectral and thermal data an octahedral geometry was assigned to the complexes with molecular formulae [Cu(C10 H24 N2 O2)2Cl2] 5H2O and [Ni(C10 H24 N2 O2)2Cl2] 2H2O. Coordination of ethylene diamine derivative to the metal ion was proposed. The anti-tubercular activity of the complexes was evaluated using Lowenstein–Jensen medium and MABA [Microplate Alamar Blue Assay] methods.